Task-Based Language (TBL) Teaching: A Method to Improve Grammar Usage for Mahaganesha Students - Ni Luh Putu Unix Sumartini; Anak Agung Ayu Meitridwiastiti (RETORIKA: Jurnal Ilmu Bahasa, 2025)
Task-Based Language Teaching (TBLT) is a student-centered approach designed to enhance language proficiency through meaningful, real-world tasks. This study investigates the implementation of TBLT to improve grammar usage, particularly the past tense, in a speaking context. The research targets first-semester pharmacy department students at Mahaganesha University. A mixed-method approach is employed, incorporating quantitative data from questionnaires and qualitative insights from interviews, with a sample of 30 participants. The study examines the effectiveness of TBLT in addressing grammar proficiency challenges and offers educators practical strategies for integrating task-based methodologies. Preliminary findings are anticipated to reveal significant improvements in students' ability to apply grammar in communicative contexts, contributing valuable insights to language instruction practices